Mapping the regulatory landscape of AI in healthcare in Africa - Townsend, Beverley Alice; Sihlahla, Irvine; Naidoo, Meshandren; Naidoo, Shiniel; Donnelly, Dusty-Lee; Thaldar, Donrich Willem (Frontiers in Pharmacology, 2023)
Artificial intelligence (AI)-enhanced technology has seen unprecedented expansion in the recent past. This growth brings with it huge opportunities for the positive transformation of the economy, business, healthcare, and society. However, a critical question is whether, and to what extent, regulatory measures and mechanisms have been implemented to safeguard its design, development, and deployment. This paper offers a scoping exercise that maps the regulatory landscape of AI in healthcare (including health research